"Twisting words"? A study of the construction and reconstruction of reliability in financial reporting standard-setting. (January 2015) - Erb, Carsten; Pelger, Christoph
Abstract: Qualitative characteristics serve to operationalise the objective of financial reporting and aim at shaping accounting discourses of standard-setters and their constituents. In the recent revision of their conceptual frameworks, the IASB and FASB decided to replace "reliability", arguably one of the most important properties of accounting, with "representational faithfulness". The aim of the present paper is to shed light on the boards' decision through a historical analysis of how reliability appeared in standard-setting and by tracing its abandonment in detail. Our study reveals that the standard-setters' construction and reconstruction of reliability attempted to undermine traditional practitioner understandings along the lines of objectivity/verifiability in order to extend the boundaries of appropriate financial reporting in the direction of current/fair values. However, as the introduction of more abstract concepts raised difficulties in reconciling the new terminology with everyday accounting practice, this turn created confusion among constituents and board members. Our paper also contributes to further our understanding about decision-making processes in standard-setting. In particular, we show how a group of board and staff members was able to establish the replacement of reliability in spite of (and partly taking advantage of) constituents' concerns and widespread confusion about the terms.